2009
DOI: 10.1007/s12665-009-0283-2
|View full text |Cite
|
Sign up to set email alerts
|

Contamination and potential mobility assessment of heavy metals in urban soils of Hangzhou, China: relationship with different land uses

Abstract: Concentration and distribution of heavy metals (Cd, Cu, Pb and Zn) in urban soils of Hangzhou, China, were measured based on different land uses. The contamination degree of heavy metals was assessed on the basis of pollution index (PI), integrated pollution index (IPI) and geoaccumulation index (I geo ). The 0.1 mol l -1 HCl extraction procedure and gastric juice simulation test (GJST) were used to evaluate the potential mobility and environmental risk of heavy metals in urban soils. The average concentration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
0
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(36 citation statements)
references
References 40 publications
1
33
0
2
Order By: Relevance
“…These correlations indicated that these metals originated from similar or co-located sources and the origin of the metals in the industrial area was highly related to the industrial activities and heavy traffic. The close relationships among Cd, Cu, Pb and Zn might indicate the combined soil pollution by multi-heavy metals as a result of long-term industrial and human activities (Lu and Bai, 2010). Table 3.…”
Section: Correlation Between the Street Dust Heavy Metal Concentrationsmentioning
confidence: 99%
“…These correlations indicated that these metals originated from similar or co-located sources and the origin of the metals in the industrial area was highly related to the industrial activities and heavy traffic. The close relationships among Cd, Cu, Pb and Zn might indicate the combined soil pollution by multi-heavy metals as a result of long-term industrial and human activities (Lu and Bai, 2010). Table 3.…”
Section: Correlation Between the Street Dust Heavy Metal Concentrationsmentioning
confidence: 99%
“…For example, soils in transportation and residential areas were characterized by higher pH and bulk density (BD) (Pouyat et al 2007;Zhao et al 2013;Yang et al 2014). Soils in urban forests (Zhao et al 2013) or protected places (Yang et al 2014) contained higher soil organic carbon (SOC), while soils at industrial sites and in transportation areas were often polluted by heavy metals (Lu and Bai 2010;Hamzeh et al 2011). At finer scales, urban soil carbon and nitrogen also varied within single patches, although this variation was smaller than that at broader scales and different land uses (Jenerette et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly Ni content in plants showed highly significant positive relationship with Cu (r = 0.918*, p < 0.05), and Pb (r = 0.902*, p < 0.05). Strong positive correlations signify that each paired elements have common anthropogenic contamination sources [48]. Other inters relationships among the constituents element of soil and plants were insignificant correlated.…”
Section: Correlation Coefficient Matrix For Heavy Metals Content Of Rmentioning
confidence: 93%